CFD modeling of transpired solar collectors and characterisation of multi-scale airflow and heat transfer mechanisms. (June 2016) - Tajdaran, Sadjad; Bonatesta, Fabrizio; Ogden, Raymond; Kendrick, Christopher
Highlights: The research has produced a numerical model for TSCs based on CFD analyses. The model allows parametric studies of key variables (e.g. wind direction). Comprehensive analysis provides more accurate simulation than previous approaches. A multi-block grid approach has been employed to resolve small-scale airflows. Findings include that wind angle has an adverse effect on the thermal performance. Abstract: Transpired Solar Collectors (TSCs) are building-integrated air-heating systems that are able to fully or partially meet the heating demands of buildings. They convert solar radiation into warm air that can either be used for ventilation, or to heat thermal storage media. TSCs are becoming an increasingly viable alternative to conventional fossil fuel-based heating systems or, more commonly, can be used in a way that is complementary to these systems such that reliance on fossil fuels is reduced. As a consequence TSCs have a potentially important role in meeting future carbon reduction goals. This research has produced a comprehensive numerical model for TSCs based on Computational Fluid Dynamic (CFD) analyses. The model allows parametric studies of key variables and is differentiated from previous models in that it takes full account of factors such as: wind speed and direction, non-uniform flow, turbulent flow, solar radiation intensity, sun position and flow suction rates. It comprises a full size section of cassette-panel TSC that can be easily morphed to reflect a wide range of geometries. A multi-block meshing approach has been employed to reduce grid size and to also resolve jet flows and boundary layers taking place in the plenum and around the absorber plate. Accuracy of the CFD model has been validated against experimental data. Modeling demonstrated that factors such as wind angle have unexpectedly significant adverse effects on system thermal performance. The studies also furthered understanding of key performance attributes including the effects of suction ratio in terms of optimising performance, and the relationship between sun angle and system operating temperature (important for effective operation of heat storage systems). Consideration of these factors is essential if the future performance of TSCs is to be optimised and the technology developed to its fullest potential.